2000
DOI: 10.1096/fj.00-0141com
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐monocyte chemoattractant protein‐1 gene therapy inhibits vascular remodeling in rats: blockade of MCP‐1 activity after intramuscular transfer of a mutant gene inhibits vascular remodeling induced by chronic blockade of NO synthesis

Abstract: Monocyte chemoattractant protein-1 (MCP-1) may play an essential part in the formation of arteriosclerosis by recruiting monocytes into the arterial wall. Thus, we devised a new strategy for anti-MCP-1 gene therapy against arteriosclerosis by transfecting an amino-terminal deletion mutant (missing the amino-terminal amino acids 2 to 8) of the human MCP-1 gene into a remote organ (skeletal muscles). Intramuscular transduction with the mutant MCP-1 gene blocked monocyte recruitment induced by a subcutaneous inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
87
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 21 publications
1
87
0
Order By: Relevance
“…Just as with CCR1, CCR5, and CXCR3, specific blockade of MCP-1/ CCR2 interaction appears possible. In experimental atherosclerosis, another disease model that is modulated by MCP-1/ CCR2, overexpression of inactive MCP-1 resulted in significant inhibition of atherosclerotic lesion formation (27,28). Similar interventions might improve allograft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Just as with CCR1, CCR5, and CXCR3, specific blockade of MCP-1/ CCR2 interaction appears possible. In experimental atherosclerosis, another disease model that is modulated by MCP-1/ CCR2, overexpression of inactive MCP-1 resulted in significant inhibition of atherosclerotic lesion formation (27,28). Similar interventions might improve allograft survival.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, our group and others have also reported that MCP-1 has a vital role in the initiation and progression of atherosclerotic or arteriosclerotic lesions in experimental animals. [17][18][19][20][21][22][23][24] Essential roles of MCP-1 and its interactions with its receptor (CCR2) in AngII-induced arteriosclerosis are shown in CCR2-deficient mice. 25 Therefore, we hypothesized that AngII increases plaque size and promotes destabilization of established atherosclerotic lesions by activating MCP-1.…”
mentioning
confidence: 99%
“…To block the MCP-1/CCR2 signal pathway, an N-terminal deletion mutant of the MCP-1 gene (7ND), which lacks the N-terminal amino acids 2 to 8, was transfected into the skeletal muscle. 17,18 This mutant MCP-1 binds to its receptor CCR2 and blocks MCP-1-mediated monocyte chemotaxis. In previous studies, we demonstrated that 7ND protein was secreted from the transfected skeletal muscle cells into the circulating blood and subsequently blocked MCP-1-induced chemotaxis in remote organs.…”
mentioning
confidence: 99%
“…We have recently reported that an N-terminal deletion mutant of human MCP-1 gene (7ND), which lacks the N-terminal amino acids 2 to 8, acts as a dominant nega-tive inhibitor for MCP-1 and blocks the MCP-1/CCR2 signal pathway in vivo (Egashira et al, 2000;Egashira, 2003). This mutant MCP-1 and normal MCP-1 form a heterodimer, which binds to the MCP-1 receptor (CCR-2) and completely inhibits MCP-1-mediated monocyte chemotaxis in vitro (Rollins, 1996).…”
mentioning
confidence: 99%